Effect of heavy metal copper on the physiological characteristics of Ulva lactuca at different temperatures - Jing Ma; Yuxin Xie; Wenjing Ge; Zhouyue Lu; Xiangwen Bao; Houxu Ding; Cheng Chen; Yaping Wu; Guoqiang Chen; Juntian Xu (Scientific Reports)
Abstract Copper (Cu) is an essential element for macroalgae and has been extensively studied, but the interactive effects of temperature and Cu on these organisms remain less understood. In this study, we measured the photosynthetic characteristics of Ulva lactuca exposed to varying Cu concentrations and different temperatures (10 °C, 15 °C, and 20 °C). The results indicated that at the same temperature, as the concentration of Cu increased, the relative growth rate of U. lactuca showed a decreasing trend. Under three different temperatures, the photosynthetic rate and chlorophyll content of the algae significantly decreased with the increase in Cu concentration. Under the same Cu concentration conditions, as the temperature rises, the RGR of the algae gradually increases. In the case of low Cu concentration (LCu), the net photosynthetic rate at 15 °C and 20 °C increased by 103.72% and 104.97%, respectively, compared to the rate at 10 °C. Under high Cu concentration (HCu), the net photosynthetic rate at 15 °C and 20 °C increased by 192.18% and 245.67%, respectively, compared to that at 10 °C. The pigment content showed a similar trend. These results indicated that under the same temperature conditions, high concentrations of Cu inhibited the growth of algae, while under the same Cu treatment conditions, a suitable increase in temperature could alleviate the toxic effects of Cu on the algae.